Peculiarities of State Experts Activity on Secret Issues of the State Penitentiary Service of Ukraine (Law and Safety, 2020)
The study is focused on the protection of state secrets in the State Penitentiary Service of Ukraine (SPS). The subject matter of scientific work is the features of state experts on secret issues, whose activities play a key role in classifying information as a state secret. The paper is aimed at analyzing the impact of numerous reforms of the SPS system on the composition and characteristics of the relevant state experts.During the research, the author has carried out the analysis of laws and bylaws, where special attention was paid to the List of officials entrusted with the functions of state experts on secret issues, and the Code of Information Constituting State Secrets. The research emphasizes that the relevance of the analysis is related not only to the already implemented changes in the system of the State Penitentiary Service of Ukraine, but also to the expectation of no less important reforms that significantly affect the structure, subordination and forms of activity of SPS agencies.As a result of the conducted analysis the author has provided characteristics to the features of quantitative and qualitative structure of the state experts which were caused by structural changes of SPS agencies. The peculiarities of the activity of state experts of SPS are characterized, such important requirements to their qualification as the corresponding experience and deep possession of the maintenance and essence of daily needs of SPS system are allocated.The obtained results substantiate the expediency of expanding the composition of state experts on secret issues in the field related to SPS of Ukraine.Based on the findings of the study, the author has offered the position of the Head of the Department for the Execution of Criminal Punishments to be included in the List of officials entrusted to perform the functions of state experts on secret issues.
Keywords: State Penitentiary Service of Ukraine; SPS of Ukraine; Ministry of Justice of Ukraine; state secret; state expert on secret issues; Code of information constituting state secrets